(Spectro)electrochemical Properties of Anthracene Containing Triarylamine Platinum(II) Acetylides. Issue 25 (15th June 2021) - Hildebrandt, Alexander; Kovalski, Eduard; Korb, Marcus
Abstract: The synthesis of [Pt2 2 (PPh3 )2 ] (5 ) (10‐ethinyl‐9‐di( p ‐anisyl)aminoanthracene=alkyne 2 H) in a cis and trans configuration was achieved. Adsorption of cis ‐5 on AlOx as well as electrochemical oxidation led to a reductive elimination of 10, 10′‐(buta‐1, 3‐diyne‐1, 4‐diyl)bis(9‐di( p ‐anisyl)amino‐anthracene) (6 ). The molecular structures of the alkyne intermediate 2 H, [Pt2 Cl(PPh3 )2 ] (4 ) and butadiyne 6 have been determined by single crystal X‐ray diffraction. Cyclic voltammetry measurements of the platinum‐acetylides trans‐ 4, and cis‐ and trans ‐5 demonstrated, that the back donation from platinum towards the π ‐system results in a shift of the triarylamine and anthracene related redox processes towards lower E °′ values, when compared to the SiMe3 ‐protected alkyne of 2 (=2 SiMe3 ). Both platinum complex trans ‐5 and butadiyne 6 demonstrated that the individual arylamine and the respective anthracenyl buildings blocks can be oxidized in four one electron processes. Spectroelectrochemical studies revealed several intense intra‐ligand absorptions in the NIR, demonstrating a high degree of delocalization in the ligand. However, a direct IVCT through the platinum was not observed. Abstract : Within this article the generation of platinum complexes containing 10‐ethinyl‐9‐di( p ‐anisyl)aminoanthracene (L ) is described. Depending on the reaction temperature the cis ‐ or trans ‐ complex of type [PtL 2 (PPh3 )2 ] was accessible. The cis ‐complex eliminates the corresponding butadiyne under electrochemical oxidation. Spectroelectrochemical studies revealed intra‐ligand CT demonstrating a high degree of delocalization in the ligand.